Possibility to use direct oral anticoagulants to prevent thromboembolic events in patients with COVID-19 - V. A. Otdelenov; K. B. Mirzaev; D. A. Sychev (Izdatelstvo OKI, 2020)
Hospitalized patients with COVID-19 who have not previously received DOAK by it is not advisable to prescribe POAC for the prevention of thrombosis in patients with COVID-19 due to the lack of clinical trial results, significant potential interactions.